Effect of Electrode Geometry on Surface Modification of Polyethylene Terephthalate by Dielectric Barrier Discharge Produced in Air at Atmospheric Pressure - Guragain, Rajesh Prakash; Joshi, Ujjwal Man; Subedi, Deepak Prasad; Baniya, Hom Bahadur (Kathmandu University Journal of Science, Engineering and Technology, 2021)
This paper presents the effect of electrode geometry on the surface modification of polyethylene terephthalate (PET) as a function of distance using 50 Hz dielectric barrier discharge at atmospheric pressure conditions. The polymer samples were treated with a Gaussian shaped electrode using a 13 kV power supply at line frequency for 1 minute. The results demonstrated that plasma treatment with a Gaussian shaped electrode improves the sample's surface wettability significantly. It is seen that there is a remarkable decrease in contact angle at the center of the sample and a relatively smaller amount of decrement away from the center of the sample.